Incidence of and mortality from kidney disease in over 600, 000 insured Swedish dogs. (20th June 2015) - Pelander, L.; Ljungvall, I.; Egenvall, A.; Syme, H.; Elliott, J.; Häggström, J.
Abstract : Kidney disease is an important cause of morbidity and mortality in dogs. Knowledge about the epidemiology of kidney disease in the dog population is valuable and large‐scale epidemiological studies are needed. The aim of the present study was to use insurance data to estimate kidney‐related morbidity and mortality in the Swedish dog population. Insurance company data from insured dogs during the years 1995–2006 were studied retrospectively. Incidence and mortality were calculated for the whole group of dogs as well as divided by sex and breed. The total number of veterinary care insured dogs was 665, 245. The total incidence of kidney disease in this group of dogs was 15.8 (15.3–16.2) cases/10, 000 dog‐years at risk. The number of dogs in the life insurance was 548, 346 and in this group the total kidney‐related mortality was 9.7 (9.3–10.2) deaths/10, 000 dog‐years at risk. The three breeds with the highest incidence of kidney disease were the Bernese mountain dog, miniature schnauzer and boxer. The three breeds with the highest mortality caused by kidney disease were the Bernese mountain dog, Shetland sheepdog and flat‐coated retriever. In conclusion, the epidemiological information provided in this study concerning kidney disease in dogs can provide valuable information for future research.